Widespread Pesticide Distribution in the European Atmosphere Questions their Degradability in Air - Mayer, Ludovic; Degrendele, Céline; Šenk, Petr; Kohoutek, Jiři; Přibylová, Petra; Kukučka, Petr; Melymuk, Lisa; Durand, Amandine; Ravier, Sylvain; Alastuey, Andres; Baker, Alex R; Baltensperger, Urs; et al. (Environmental science & technology, 2024)
Risk assessment of pesticide impacts on remote ecosystems makes use of model-estimated degradation in air. Recent studies suggest these degradation rates to be overestimated, questioning current pesticide regulation. Here, we investigated the concentrations of 76 pesticides in Europe at 29 rural, coastal, mountain, and polar sites during the agricultural application season. Overall, 58 pesticides were observed in the European atmosphere. Low spatial variation of 7 pesticides suggests continental-scale atmospheric dispersal. Based on concentrations in free tropospheric air and at Arctic sites, 22 pesticides were identified to be prone to long-range atmospheric transport, which included 15 substances approved for agricultural use in Europe and 7 banned ones. Comparison between concentrations at remote sites and those found at pesticide source areas suggests long atmospheric lifetimes of atrazine, cyprodinil, spiroxamine, tebuconazole, terbuthylazine, and thiacloprid. In general, our findings suggest that atmospheric transport and persistence of pesticides have been underestimated and that their risk assessment needs to be improved.
Keywords: pesticides; risk assessment; transport; degradation; atmosphere